Lifting symmetric pictures to polyhedral scenes - Kaszanitzky, Viktória E. (Ars mathematica contemporanea, 2017)
Scene analysis is concerned with the reconstruction of ?$d$?-dimensional objects, such as polyhedral surfaces, from ?$(d-1)$?-dimensional pictures (i.e., projections of the objects onto a hyperplane). In this paper we study the impact of symmetry on the lifting properties of pictures. We first use methods from group representation theory to show that the lifting matrix of a symmetric picture can be transformed into a block-diagonalized form. Using this result we then derive new symmetry-extended counting conditions for a picture with a nontrivial symmetry group in an arbitrary dimension to be minimally flat (i.e., "non-liftable"). These conditions imply very simply stated restrictions on the number of those structural components of the picture that are fixed by the various symmetry operations of the picture. We then also transfer lifting results for symmetric pictures from Euclidean ?$(d-1)$?-space to Euclidean ?$d$?-space via the technique of coning. Finally, we offer some conjectures regarding sufficient conditions for a picture realized generically for a symmetry group to be minimally flat.
Keywords: dvig; incidenčna struktura; poliedrski sestav; simetrija; slika; stožčenje